SYSTEMATIC LITERATURE REVIEW OF TRENDS AND DEVELOPMENT IN ANTIHYPERTENSIVE EFFECT OF SEAWEED RESEARCH: SCIENTOMETRIC ANALYSIS - Yosie Andriani; Jasnizat Saidin; Noraznawati Ismail; Mohamad Gazali (ALOTROP, 2024)
Hypertension is the most alarming disease that causes cardiovascular risk for human health Worldwide. Thus, the author has explored marine natural marine macroalgae that possess antihypertension activity to lower blood pressure. Marine macroalgae or seaweed tropical marine organisms from marine biodiversity that are distributed widely in the subtropic and tropical oceans. Marine macroalgae have a significant role in preventing hypertension risk with a unique biochemical compound that is not contained in a terrestrial plant. However, antihypertension of seaweed research using scientometric analysis is limited. This study collected scientific information from relevant literature to determine the recent development and trends regarding antihypertension of seaweed research Worldwide. Many researchers, academia, and practitioners will have a wide understanding of the recent novelty finding in seaweed prospect to prevent antihypertension disease with a scientometric analysis approach to interpret data using CiteSpace. The literature review using scientometric analysis regarding antihypertension of seaweed research from 1991 until 2022. The result showed Suetsuna K is the most influential author (sigma score =1.52, centrality score =0.24 and degree score =51). Advances in Food and Nutrition Research is the leading journal. The most popular keywords in common cluster related antihypertension of seaweed research area are seaweed, hypertension, algae, in vitro, and dietary fiber. On the other hand, various stakeholders need to know the development and trends of a marine drug for antihypertensive effect from various seaweeds or marine macroalgae.